Envelhecendo com HIV/Aids e enfrentamentos nas relações afetivo-sexuais - Pedroza, Ariadne Pereira (2013)
The progress of the technologies, the access to medicines for the erectile dysfunction, the use of prostheses and the resistance in using preservative checks a new epidemic profile of the acquired immune Deficiency Syndrome (aids), in the last years, with the increase of its incidence in individuals with same age or above 50 years. Differently of the beginning of the aids epidemic, when to the infected individual if they imposed narrow limits about its life planning, the current reality has been making possible several forms of living together with HIV and the disease. The matrimonial relationship is one of them. Leaving of the presupposition that more and more individuals are aging and contaminating themselves with HIV, after the 50 years of age, and of the possibility to form affective-sexual relationships, it was decided to approach the referring aspects to the facing lived by the age group. For that, it was listed the following objectives: to analyze the people's facing that age with HIV/Aids in the context of the affective-sexual relationships; to check the people's facing forms aging with HIV/Aids; and to identify the people's affective-sexual relationships aging with HIV/Aids. It is a descriptive study, of qualitative approach, accomplished in the period of July to September of 2012, with 10 participants bearers of HIV of a health service of state reference in infectious diseases in João Pessoa/PB. The data were collected through an interview route with tape recorder use and the thematic content analysis technique proposed by Bardin (2011). Starting from the data, five analysis categories and their respective subcategories emerged, to know: 1. aging with HIV/Aids, 2. Forms Facing form of HIV/Aids, 3. Affective-sexual Relationships, 4. Infection types and 5. Sexual practices. The study watched the positive and negative aspects of aging being soropositive for HIV and facing lived in that context, as the denial, the isolation, the acceptance, the adaptation, the prejudice and the discrimination. The affective-sexual relationships involve family facing and in the partnerships, being the family recognized as a support unit also opposing of abandonment before the social facing imposed by the disease. In the relationship with the partners the facing involve the preventive and do not preventive sexual practices, that associated to the knowledge and ignorance on the infection types are configured as aspects to be considered to the vulnerability to HIV. The couples that are aging with HIV/Aids in heterosexual partnership present important peculiarities that request specialized attendance, orientation and advising back to an integral and preventive approach about sexuality and the vulnerability to HIV in the context of that relationship